Association between perinatal depressive symptoms and parental cohabitation status in a Nordic high-income country - Iliana Liakea; Natasa Kollia; Malva Nord; Emma Fransson; Maja Bodin; John L. Cox; Emma Bränn; Alkistis Skalkidou (PLoS ONE, 2026)
Change in cohabitation status could influence the economic security and well-being of parents and their children. However, literature concerning the association between the duration of perinatal depression (PND) exposure and change in parental cohabitation status is limited. Therefore, this study aimed to assess whether the presence and persistence of maternal PND symptoms are associated with changes in parental cohabitation status up to six years postpartum. Using data from 4,344 persons in the Swedish BASIC and U-BIRTH cohort studies, maternal depressive symptoms were assessed at three time points (during pregnancy, 6 weeks, and 6 months postpartum) using the Edinburgh Postnatal Depression Scale. Cohabitation status was measured at 6 weeks and 6 years postpartum. Logistic regressions estimated odds ratios (ORs) for non-cohabitation associated with the number of PND-positive time points. Mothers with positive screenings at more than one time point for depressive symptoms had higher odds of not cohabiting at both 6 weeks and 6 years postpartum. At 6 years, mothers with depressive symptoms at all three time points had over four times the odds of not cohabiting (OR 4.1, 95% CI 1.7–9.5). However, most associations lost significance after full adjustment for sociodemographic and psychosocial factors, except the association between prolonged PND (3 positive screenings) and non-cohabitation at six years postpartum. Prolonged PND symptoms may increase the risk of long-term parental separation. Although confounding factors reduce the strength of this association, findings underscore the need for extended mental health monitoring and support for perinatal persons.